Sopostavlenie kulʹtur čerez posredstvo kategorii “Kommunikativnyj ideal” - Dementʹev, Vadim V.; Rogačëva, Natalâ B. (Stylistyka, 2021)
The article is devoted to researching cultures through a communicative ideal or absolu[1]te commun ,ative value that covers the culture’5 basic communication rules shared by all speakers. This absolute ideal determines the concept of “good” and “bad” speech and is invariably considered when any language or speech unit is used. The intentional structure, themes and style of the communicative ideal cover all types, forms and genres of phatic and non-phatic communication. Communicative ideal also de[1]termines the poetics of human communication within this culture. It s possible to discover a communicative ideal through the language idioms which are formed by lexical units of the language naming the key value concepts of this culture. Good material can also be gained from various reflexives or metalanguage comments, phrases about the language and speech which belong to various spheres and types of com[1]munication. It may also be valuable to study the characters of national (Russian, English, Polish) li[1]terature who may be viewed as the models of the ideal communicative partners within these cultures. The article discusses the probability of experimental study of a communicative ideal. It is also important that a communicative ideal occupies a significant place in the system of statements about the types of the national cultures which are formulated in a semantic pri[1]mitive language. Thus, commun.. ative ideal is formed by values described in a semantic primitive language through simple affirmative formulas: “It’s good if...” Communicauve ideal as a rule is rather simple and clear for every speaker and is usual[1]ly not an object of description and discussion. This mainly dirferentiates the communica[1]tive ideal from various communicative scenarios. However, a communicative ideal can also vary, at least, in some cultures. The typology of communicative concepts and values based on the field model where the centre corresponds with the communicative ideal and the periphery - particular communicative scenan >s, enables to learn different types of communicative concepts va ation for the centre and periphery.